Thoracic aorta aneurysm- a rare cause of chronic backache with mediastinal shadow: case report - Mathur, Akash; Gangopadhyay, Devleena; Daga, Ashutosh; Saxena, Puneet; Malhotra, Hemant (International Journal of Scientific Reports, 2018)
Thoracic aortic aneurysms (TAA) are rarely symptomatic. A 55 year old male presents with longstanding chronic backache. CXR showed left hilar shadow with collapse of left lung. Considering the CXR findings and with the patient being chronic smoker a strong possibility of carcinoma lung with bony metastasis was kept and further CECT chest was done. The CECT chest was suggestive of a thoracic aorta aneurysm with thrombosis compressing left principal bronchus and its lower lobar branch resulting in distal area of collapse and consolidation of left lower lobe. These findings were further confirmed on CT angiography. The patient was thus diagnosed as a case of descending thoracic aorta aneurysm probably of atherosclerotic etiology with thrombosis. Patient was started on beta blockers and ACE inhibitors along with supportive and symptomatic treatment and was further transferred to the department of CTVS for surgical intervention. Thus, this case report here signifies that possibility of thoracic aorta aneurysm should always be considered in a patient with chronic backache specially in presence of mediastinal shadow on CXR.